Electrochemical determination of tramadol using modified screen printed electrode - Sayed ali Ahmadi (International Association of Physical Chemists (IAPC), 2021)
The detection of tramadol using a screen printed electrode modified with La3+/ZnO nano-flowers and multi-walled carbon nanotubes (La3+/ZnO NFs-MWCNTs/SPE) is reported in this work. In order to examine tramadol electrochemical oxidation, the modified electrode was implemented with the utilization of differential pulse voltammetry, chronoamperometry and cyclic voltammetry as diagnostic techniques. The proposed electrode displays favorable electrocatalytic behavior concerning tramadol oxidation with an approximately 330 mV potential shift to a lesser positive potential. In the 0.5 to 800.0 μM range for tramadol, differential pulse voltammetry displays linear dynamic activity. Tramadol detection limit of 0.08 μM was derived within optimized testing conditions for this simple construction sensor. Lastly, this fabricated sensor was utilized with desirable results to determine tramadol in tramadol samples and urine samples.